Voices of Parents about their Out of School Children with Disabilities - Manzoor, Afaf; Hameed, Abdul; Nabeel, Tanzila (JIE, 2018)
In Pakistan, about six million children are out of school at primary level.30 percent of them are with disabilities. Such a huge number of children create a gigantic challenge for the government to meet the target of 100% school enrollment. A closer look at the levers of exclusion indicates that there are economic, cultural and structural barriers to keep children out of school. Unless these barriers are addressed, the dream of every child to be in school cannot come true. Any educational plan that discount children with disabilities will doom to fail. Thisstudy investigates the perceptions of parents about the value of education. The purpose of the study was to collect feedback from the prime stakeholders in their own context. 433 parents of children with disabilities were selected from two districts of Punjab to document their voices about the educational exclusion. Data was collected through the interview cum questionnaire. The results of the study revealed that the majority of the parents were positive towards education of their children. Lack of school readiness, distance from special schools and poverty were reported as major barriers to education. It was argued that inclusive education is the only way forward.